Kesadaran Body Positivity Dalam Film Imperfect - Larasati, Ukhti Tri; Hamzah, Radja Erland; Saifulloh, Muhammad (Brand Communication, 2025)
The phenomenon of self-acceptance or self-love is increasingly relevant in today's society. The beauty standards formed in the community often lead individuals to feel less confident about themselves, which can negatively impact their self-image. In response to this issue, the concept of body positivity has emerged as a form of self-acceptance and a positive view of one's own body. These body positivity values are disseminated through various mass media, including films. The film "Imperfect" is one such medium that addresses themes related to body positivity.This study aims to analyze body positivity awareness through a reception study among students. The research employs Stuart Hall's reception analysis approach, utilizing primary data from direct interviews and secondary data from relevant literature studies. The findings of this research indicate that reception varies depending on the information and knowledge received by an individual. In the reception study of the film "Imperfect," most informants viewed body positivity as a positive self-view. The analysis using Stuart Hall's reception theory revealed that two informants held a dominant hegemonic position, one informant was in a negotiating position, and two informants were in an oppositional position.